Analisis Information Quality Dan Consumer Trust Pada Purchase Intention Dengan Social Psychology Di Tiktokshop - Fadlurahman, Luthfi; Indriya Himawan, Abdurrahman Faris (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2024)
Background –Increasing customer awareness of goods and services means that internet use has an influence in generating consumer responses. The role of the internet is to function as a communication and information medium, which can then be used as a medium for carrying out electronic commerce activities or referred to as e-commerce. Aim – This study aims to measure the level of service, trust, social psychological distance, and consumer purchase intentions for products sold on the Tiktok platform. Design/ Methodology/ Approach – This study uses quantitative methods by using a questionnaire as a data collection medium with 200 respondents acting as the sample in this study. Findings – This study obtains an understanding that Information Quality and Trust have a significant and positive influence on Purchase Intention through Social Psychological Distancing on the TikTok e-commerce platform. Conclusion – Tiktok indicates that there are problems with information quality and trust which are mediated by social psychology which has the potential to influence consumer purchase intention. Research Implication – In the next study, it is expected to measure other variables, not only on information quality and trust, and can conduct research not only social psychological distancing as mediation. Limitations – This research uses a quantitative approach in obtaining data and answering problems, especially in seeing consumer buying interest